2021
DOI: 10.3390/ijms22020679
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Protaetia brevitarsis seulensis’ Water Extract on Trimethyltin-Induced Seizures and Hippocampal Neurodegeneration

Abstract: This study aimed to investigate whether the Protaetia brevitarsis seulensis (PB)’ water extract (PBWE) ameliorates trimethyltin (TMT)-induced seizures and hippocampal neurodegeneration. To investigate the potential neuroprotective effect of the PBWE in vitro, a lactate dehydrogenase (LDH) assay was conducted in TMT-treated primary cultures of mouse hippocampal neurons. In TMT-treated adult C57BL/6 mice, behavioral and histopathological changes were evaluated by seizure scoring and Fluoro-Jade C staining, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 49 publications
4
27
0
1
Order By: Relevance
“…The cetoniid beetle Protaetia brevitarsis (PB) (Coleoptera: Scarabaeidae) is an easy-to-raise litter-feeding soil insect that can convert decaying plant biomass into frass with a high humic acid (HA) content [1][2][3]. Beyond converting agricultural waste, the mature PB larvae (PBLs) have other beneficial economic effects: (1) the processed mature larva is a traditional medicine that has many benefits for human health [1,[4][5][6][7][8], and (2) the mature larva contains high-quality fat and protein, which can be considered a future feed and food source [9]. Therefore, PB and its application have recently become a meaningful research subject.…”
Section: Introductionmentioning
confidence: 99%
“…The cetoniid beetle Protaetia brevitarsis (PB) (Coleoptera: Scarabaeidae) is an easy-to-raise litter-feeding soil insect that can convert decaying plant biomass into frass with a high humic acid (HA) content [1][2][3]. Beyond converting agricultural waste, the mature PB larvae (PBLs) have other beneficial economic effects: (1) the processed mature larva is a traditional medicine that has many benefits for human health [1,[4][5][6][7][8], and (2) the mature larva contains high-quality fat and protein, which can be considered a future feed and food source [9]. Therefore, PB and its application have recently become a meaningful research subject.…”
Section: Introductionmentioning
confidence: 99%
“…VC, animals receiving corn oil and PBS; BPH, animals receiving TP and PBS; Fin, animals receiving TP and finasteride; BPH + PBE 12.5, 25, and 50, animals receiving TP and PBE at rates of 12.5, 25, and 50 mg/kg, respectively; PBE, animals receiving only PBE (50 mg/kg). Data are presented as mean ± standard deviation (SD) (n = 6) (Lee et al, 2021). There results indicated that PBE, as antioxidant, may be a therapeutic material for treating BPH.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds known to have biological activities including antiproliferative and antitumor effects (Dinesh et al., 2012 ). We further investigated that inosine and benzoic acid have significant antioxidative activity in a dose‐dependent manner using our screening system (Lee et al., 2021 ). There results indicated that PBE, as antioxidant, may be a therapeutic material for treating BPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dried T. angustipennis MO were purchased from the Kwang Myong Dang Co. (Ulsan, Korea) and were morphologically and genetically identified according to a method described in a previous study (Lee et al . 2021b). The samples (Manufacturer No.…”
Section: Methodsmentioning
confidence: 99%